CURA PERSONALIS: SIKAP PASTORAL GEREJA BAGI PENDAMPINGAN KAUM LGBTQ KRISTIANI - Suwito, Benny (Bahasa Indonesia, 2024)
The Church is the people of God. And as people of God, the Church consists of all people who believe in Christ. People of God with LGBTQ are people who have faith in. Christ. They accept Christ as the savior but need help understanding their condition. Thus, they need to be helped as people of God because some faithful cannot get them into the Church. They think that people with LGBTQ inclinations are not genuine or even sinful. This article would like to explore how the Church must serve all people who believe in Christ and how the Church can assist them by providing good accompaniment. Consequently, it will seek an explanation based on literature studies conducted on the main concepts in this research, namely “cura personalis” and LGBTQ. After that, this article will develop a pastoral attitude for assisting LGVTQ people as a theological reflection based on the study of moral theology and ecclesiology, which distinguish "actions" and "attitudes" towards other people, the meaning of being a Christian which is in line with the understanding of Christian Anthropology which states that humans are the image of God who has a purpose in life to be called to holiness, and about the position of Christians as part of God's people. That understanding will open a new way in pastoral care, not to contra the doctrine of the Church but to build a bridge to receive the LGBTQ people in the Church as the same people of God who journey on earth.